Green Purchase Intention in Slow Fashion: A Conceptual Framework - Ghina Alya Audina; Nurafni Rubiyanti; Arry Widodo; Anita Silvianita (International Journal of Scientific Multidisciplinary Research, 2024)
This study aims to explore the connection between environmental concern, environmental knowledge, eco-innovation, green products, and consumer attitudes towards green purchase intentions using data from Generation Z in West Java. The research model employs structural equation modeling (SEM) with a partial least square (PLS) method. The findings indicate that environmental concern, environmental knowledge, eco-innovation, and green products positively influence green purchase intentions, with consumer attitudes serving as a mediating factor in this relationship